Application of Natural Plant Growth Regulator to Improve Growth and Yield of Shallot Lembah Palu Variety - Kurniawati, Dwi; Bahrudin, Bahrudin; Anshar, Muhammad (Mitra Sains, 2021)
This study aimed to determine the effect of source and concentration of natural PGR on growth and yield of shallot Lembah Palu variety and interaction between these factors. This research was conducted from May to August 2019 in Sidera Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi, and used a Randomized Block Design (RBD) with two factors and three replications. The first factor was the different sources of natural PGR (J) consisting of 2 (two) treatments: J1 (coconut water) and J2 (moringa leaf extract). The second factor was the concentration of PGR (K) consisting of 5 (five) levels: K1 (20%), K2 (40%), K3 (60%), K4 (80%), and K5 (100%). Data were analyzed using ANOVA and followed by a DMRT test 5%. The results showed that there was an interaction between the source and concentration of PGR number of tillers at age 45 DAP, the number of tubers per clump, and the fresh weight of tubers per clump. Coconut water with a concentrate of 40% was the treatment that provided the highest result. Source of PGR had a statistically significant effect on fresh and dry leaves at age 15 DAP, total fresh and dry weight at age 15 DAP, and total leaf area per plant at age 15 DAP. Coconut water was the treatment that provided the highest result. The concentration of PGR had a significant effect on fresh leaf weight and total fresh weight per plant at age 25 DAP. Concentrate 20% was the treatment that provided the best result.